An evidence review from Australia, Aotearoa/New Zealand and Canada for the WA Aboriginal Sexual Health and Bloodborne Viruses Strategy - Rosenberg, Shoshana; Lobo, Roanna; Hallett, Jonathan (2019)
This review was commissioned by the Department of Health WA as part of the development process for the fourth WA Aboriginal sexual health and blood-borne virus (SHBBV) strategy (2019–2023). This strategy aims to prevent and reduce rates of infection in Australian communities.This review has followed the structure of the third strategy, analysing the data through each domain: prevention and education; testing and diagnosis; disease management and clinical care; workforce development; enabling environments, and; research, evaluation, and surveillance. The review aims to provide a broad overview of evidence on the way SHBBV health promotion, care, and research are negotiated with Aboriginal populations across three countries: Aotearoa/ New Zealand, Australia, and Canada. The data were collected through a scoping review of academic and grey literature (2005-2018), and further developed with the guidance of an advisory group. Culturally appropriate reviews can provide inroads to more constructive policy-making and research practices in health [45, 46]. Reviews can help to address the gaps in inclusive practice guidelines that are evident in current Australian Aboriginal health strategies, in part due to significant knowledge gaps [47]. In particular, reviews which utilise ‘decolonising methodologies’ (such as stakeholder consultation and the expansion of what can be considered ‘valid’ knowledge) can include research that is informed by the needs of communities, as well as the data collected through standard literature searches [48]. Decolonisation, the positioning of Aboriginal-led frameworks at the fore of service delivery, is a crucial aspect of positive and constructive health care, promotion, and research for Aboriginal people [49-51]. It involves directly engaging affected communities, keeping Aboriginal voices amplified and considered throughout institutional processes, practicing reflexivity and immersion, and ensuring that any research or health care/promotion outcomes are addressed with an Aboriginal lens in mind [51-53].